Assessment of Thyroid Dysfunction as a Predisposing Factor for Asymptomatic Bacteriuria in Women of Reproductive and Postmenopausal age - Haghighi , Mehrdad; Goudarzi, Mehdi; Shabani, Minoosh; Miri, Mirmohammad (Novelty in Biomedicine, 2023)
Background: Infectious diseases are associated with thyroid autoimmune disorders, mainly. Meanwhile, thyroid gland function as a risk factor for infectious diseases is a challenging debate topic that needs more evaluation. Considering the high burden of hypo and hyperthyroidism in many regions of the world and the consequences of these disorders on different aspects of human health, evaluating and screening high-risk populations and treating patients is of great importance. In the present research, we investigated any association between thyroid dysfunction and asymptomatic bacteriuria in women of reproductive and postmenopausal age. Materials and Methods: The study was performed for six years (between 2015-2021) in Tehran, Iran. Our study enrolled 188 women of reproductive and postmenopausal age with and without asymptomatic bacteriuria. All participants’ thyroid stimulating hormone (TSH) and free T4 levels were evaluated. The association between thyroid dysfunction and asymptomatic bacteriuria was assessed. Results: The mean level of TSH in all culture-positive samples was 2.39, while it was 3.11 in culture-negative samples (P value < 0.05). The mean TSH level was 2.4 and 2.3 in Escherichia coli and Non- E. coli positive urine cultures, respectively (P value= 0.67). Asymptomatic bacteriuria was significantly more common in patients with lower TSH levels. The mean level of free T4 in all participants was 8.21, with maximum and minimum levels of 12.3 and 4, respectively. Also, the mean level of free T4 in all culture-positive samples was 9.53, while 7.13 in culture-negative samples (P value=0.09). The mean free T4 level was 9.36 and 10.03 in E. coli and Non-E. coli positive urine culture respectively (P value= 0.35). Conclusion: Our study revealed a significant correlation between the population’s TSH level and asymptomatic bacteriuria. Also, it showed no significant association between TSH level and any specific uropathogenic.